2016
DOI: 10.3109/09638288.2016.1138548
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participation in family and recreational activities of young children with cerebral palsy

Abstract: Supporting children's adaptive behaviour, family ecology, and access to community recreational programmes may foster participation in family and recreational activities for young children with CP. Implications for Rehabilitation Participation in family and recreational activities for young children with CP is complex and influenced by child, family and environmental factors. Practitioners are encouraged to support children's adaptive behaviour and access to community programs and family relationships, involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
40
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 49 publications
8
40
2
2
Order By: Relevance
“…The impact of children's environments on their health and well‐being, including their participation in everyday activities, is well documented . Although recent studies suggest disparities in caregiver perceptions of environmental support, this study contributes new knowledge about the impact of perceived environmental support on the participation of young children across a broader age range (0–5y) and abilities . Main study findings confirm the hypothesis that caregiver perceptions of home environmental support mediate the relationship between child and/or family factors and home involvement.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The impact of children's environments on their health and well‐being, including their participation in everyday activities, is well documented . Although recent studies suggest disparities in caregiver perceptions of environmental support, this study contributes new knowledge about the impact of perceived environmental support on the participation of young children across a broader age range (0–5y) and abilities . Main study findings confirm the hypothesis that caregiver perceptions of home environmental support mediate the relationship between child and/or family factors and home involvement.…”
Section: Discussionsupporting
confidence: 77%
“…This may have been due to timing data collection during summer months, when time use at home may fluctuate owing to improved weather conditions and/or variable family schedules. Alternatively, children's participation frequency may vary during early childhood and/or according to the child's functional severity, as has been shown recently in a similar study involving young children with cerebral palsy . Finally, the cross‐sectional design precludes conclusions about cause–effect relationships between concurrent child and family factors, environmental support, and home participation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Unlike other research where services have not been found to predict outcomes in children with CP, in this study we did find significant relationships, perhaps because of the detailed collection of services provided. The significant school‐based services to the student (with the student present) reported accounted for approximately 4% to 14% of the variance in the SFA outcomes, determined by subtracting the variance accounted for by the covariates from the variance with covariates and services.…”
Section: Discussioncontrasting
confidence: 99%